Relationship of Career Mentoring and Socioeconomic Origin to Managers' and Professionals' Early Career Progress - Whitely, William; Dougherty, Thomas W.; Dreher, George F. (Academy of Management Journal, 1991)
This study examined the relationship of career mentoring to the promotions and compensation received by 404 early career managers and professionals working in a variety of organizations. The results indicate that with a number of variables controlled, career mentoring was related to both promotion rate and total compensation. The results also support the conclusion that career-oriented mentoring has a greater relationship with promotion rate for people from the highest-level socioeconomic backgrounds than for those from lower-level backgrounds. We provide several explanations for the effects of career mentoring on early career progress and suggest a number of areas for future research on mentoring and other developmental relationships.